Pengaruh waktu pemberian jerami kacang tanah (Arachis hypogaea)sebagai pakan sumber protein terhadap kecernaan jerami jagung (Zea mays) pada kambing - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Studies were made to investigate the appropriate time of protein source feeding to maximized roughage digestibility. Furthermore the effect of protein supplementation on roughage digestibility was studied. The studies were done in two steps, using Completely Randomized Block Design. Twelve ettawa cross breed, 8 months of age were randomly into 6 groups of 2 namely K-1 was fed 100% corn stover, K-2 66,6% corn stover + 33,4% peanut straw, K-3 33,4% corn stover +66,6% penaut straw. K-4 and K-5 were fed same as K-2 and K-3 but peanut straw was given in the afternoon after fed them with corn stover in the morning, while K-2 and K-3 were fed peanut straw in the morning and corn stover in the afternoon. K-6 was fed 100% peanut straw. Total collection method was used to measure the digestible dry matter, digestible organic matter, digestible protein and digestible energy. The results showed that there no significantly different between corn stover as the only feed and corn stover (K-1) with peanut straw both before or after peanut straw was given (K-2 and K-3) or (K-4 and K-5) on digestiblke organic matter (44.68